AN EVALUATION OF VIDEO MATERIALS WITH A HEALTH-RELATED MESSAGE AVAILABLE IN INDONESIA - Mukisa, Ronald; Sinaga, Doni Marisi; Macnab, Andrew (Proceedings of the International Conference on Applied Science and Health, 2019)
Background:  A core component of health promotion involves education. When we educate children and their parents about health, we need to use words that they can understand and ways to teach them that they find interesting. In schools in Uganda we have found that many children learn important facts from music videos recorded by celebrities that include a health message. This study looked at video material with a health message that is available on-line in Indonesia for those involved in health promotion to use to educate parents and children.Methods: A google question was generated and the videos the respondents suggested were then viewed on YouTube to identify the health topics that they contained. From this search, the availability of other videos with similar or related messages was evaluated.Results: Nine respondents suggested videos with a health message; 8 were female and 1 male, all had a bachelor?s or master?s degree. Four of the videos identified contained general health related messages, the remainder were specific to one of two areas, handwashing and hygiene (3) or tooth brushing and oral health (2). Importantly, when viewing these videos, a large number of related videos in various formats (message for adults/parents, message for children, educational material, songs, cartoons) were cross linked with the targeted video.Conclusion: In Indonesia, a broad range of videos exist that can be used either to educate parents and children about the key health topics that these videos cover, or to act as a model for producing similar materials for newly identified health promotion issues. Engaging and educating parents and children is an important health promotion strategy and community empowerment approach  to improving the determinants of health.